International Constraints and Electoral Decisions: Does the Room to Maneuver Attenuate Economic Voting?. Issue 3 (6th June 2018) - Kosmidis, Spyros
Abstract: Prominent studies of electoral accountability and economic voting suggest that government constraints and international financial structures decrease the economic vote. The proposed mechanism is often labeled as the "room to maneuver, " and it posits that because elected officials have limited space to propose and implement economic policy, politicians can shirk responsibility, and thus voters are less likely to place voting weights on the economy. However, results from elections that took place in Europe during the Great Recession and scholarly research on economic voting in these elections cast serious doubts on the causal mechanism. This article directly tests this mechanism with a survey experiment using data from Greece (the country most affected by the debt crisis). The results suggest that although the economic vote is strong and substantive, its size does not vary across the room to maneuver treatments. This finding informs the literature on economic voting and carries out important implications for party strategies with respect to exogenous policy impositions and their electoral effects.